2015
DOI: 10.1093/annonc/mdu571
|View full text |Cite
|
Sign up to set email alerts
|

TEMHEAD: a single-arm multicentre phase II study of temsirolimus in platin- and cetuximab refractory recurrent and/or metastatic squamous cell carcinoma of the head and neck (SCCHN) of the German SCCHN Group (AIO)

Abstract: NCT01172769.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 25 publications
0
38
1
1
Order By: Relevance
“…Mutational analysis in our study revealed a low incidence of PIK3CA (9%) without a correlation with treatment efficacy [13]. Clearly, other predictive biomarkers are needed in order to individualise therapy in R/M SCCHN.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Mutational analysis in our study revealed a low incidence of PIK3CA (9%) without a correlation with treatment efficacy [13]. Clearly, other predictive biomarkers are needed in order to individualise therapy in R/M SCCHN.…”
Section: Discussionmentioning
confidence: 60%
“…Patients' sera were collected within the TEMHEAD phase II study (NCT01172769), which tested temsirolimus as a weekly intravenous infusion until death, progression or intolerance [13]. From a total of 40 eligible patients, 29 had assessable sera for this preplanned substudy.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these phase II results should be viewed with caution but could represent the beginning of a new treatment strategy targeting the PI3K pathway. Mechanistic target of rapamycin (mTOR) represents another potential target in the PI3K pathway, and mTOR inhibitors have shown preliminary efficacy preclinically and clinically, including in the TEMHEAD phase II study [24,25,26]. Other trials were negative including another phase II trial with the pan-PI3K inhibitor PX-866 and a phase II trial with the mTOR inhibitor everolimus as monotherapy [27,28].…”
Section: Targeted Therapies In Head and Neck Cancermentioning
confidence: 99%
“…Generally, PIK3CA mutations, amplifications, or PTEN loss could mechanistically be expected to predict sensitivity to PI3K pathway inhibitors. In clinical studies in HNSCC, these aberrations were infrequently or not at all identified, and the small sample size did not allow for correlative analyses [26,27,28]. In a retrospective study in 549 patients with breast cancer, mutations in PIK3CA or AKT and PTEN loss were associated with an improved response to everolimus compared to the ‘PI3K normal pathway' [58].…”
Section: Predictive Biomarkersmentioning
confidence: 99%